Enhancement of post-activation performance enhancement by blood flow restriction following specific on-ice exercise program in ice hockey players - Gabrys, T.; Chruscinski, R.; Szmatlan-Gabrys, U.; Garnys, M.; Bichowska-Paweska, M.; Cepicka, L. (Frontiers in Sports and Active Living, 2025)
Introduction: Due to the requirements for research on motor skills in elite hockey players, an attempt was made to assess the skills following the application of PAPE and BFR-enhanced PAPE to enhance lower limb power.